Monocytes Elicit a Neutrophil-Independent Th1/Th17 Response Upon Immunization With a Mincle-Dependent Glycolipid Adjuvant - Desel, Christiane; Murray, Peter J.; Lehmann, Christian H. K.; Heger, Lukas; Christensen, Dennis; Andersen, Peter; Mack, Matthias; Dudziak, Diana; Lang, Roland (Frontiers in Immunology, 2022)
Successful subunit vaccination with recombinant proteins requires adjuvants. The glycolipid Trehalose-dibehenate (TDB), a synthetic analog of the mycobacterial cord factor, potently induces Th1 and Th17 immune responses and is a candidate adjuvant for human immunization. TDB binds to the C-type lectin receptor Mincle and triggers Syk-Card9-dependent APC activation. In addition, IL-1 receptor/MyD88-dependent signaling is required for TDB adjuvanticity. The role of different innate immune cell types in adjuvant-stimulated Th1/Th17 responses is not well characterized. We investigated cell recruitment to the site of injection (SOI) and to the draining lymph nodes (dLN) after immunization with the TDB containing adjuvant CAF01 in a protein-based vaccine. Recruitment of monocytes and neutrophils to the SOI and the dramatic increase in lymph node cellularity was partially dependent on both, Mincle and MyD88. Despite their large numbers at the SOI, neutrophils were dispensable for induction of Th1/Th17 responses. In contrast, CCR2-dependent monocyte recruitment was essential for induction of Th1/Th17 cells. Transport of adjuvant to the dLN did not require Mincle, MyD88 or CCR2. Together, adjuvanticity conferred by monocytes can be separated at the cellular level from potential tissue damage by neutrophils.